Isolation, identification and pathogenicity study of pathogens during postharvest storage of sweet cherries - WANG Fengli; QIU Jiying; DAI Meixue; CHEN Leilei; ZHAO Shuangzhi; XIN Xue; ZHOU Qingxin (浙江大学学报. 农业与生命科学版)
Six pathogens were isolated from postharvest sweet cherries during the transportation and low-temperature storage. They were Alternaria alternata NCPS1 and NCPS2, Alternaria sp. NCPS3, Penicillium expansum NCPS4, Cladosporium herbarum NCPS5 and Sarocladium terricola NCPS6. Then, the biological characteristics of the six pathogens were studied in three aspects of growth rate, growth temperature and growth pH value. The results showed that the optimum growth temperature of NCPS1, NCPS2, NCPS3, NCPS5 and NCPS6 was 25 ℃, and the optimum pH value was 8. The optimum temperature of NCPS4 was 30 ℃, and it could grow at pH 2-10. Only NCPS1 and NCPS2 could grow at the low temperature of 0 ℃. The results of pathogenicity study showed that the six strains could be divided into strong pathogenic strains of NCPS1, NCPS2, NCPS3, moderate pathogenic strains of NCPS4 and NCPS5, weak pathogenic strains of NCPS6. In a word, it provides a scientific theory basis for the development of low-temperature storage and fresh-keeping technology of the postharvest sweet cherries.